please show the work
write the equation described in slope-intercept form: (ab, 3b + 1)
Let's go little bit further.
x = ab therefore b = x/a ------------------(1)
y = 3b + a therefore b = (1/3)(y-1) ------(2)
From equation (1) and (2),
(1/3)(y-1) = x/a rearrange this equation gives
y = (3/a)x + 1
Therefore when x=0, y = 1 (Y intercept) and when y=0, x = -a/3 (X intercept)
Basic slope-intercept form is y=mx+b. It looks like you are given coordinates (ab, 3b+1).
x = ab, y=3b+1, m=slope, and b=y-intercept. With substitution slope-intercept form is...
3b+1 = m(ab) + b
You can then continue to simplify the equation as needed.